Analisis Bibliometrik terhadap Hubungan Berpikir Kritis dan Kecemasan Matematika dalam Literatur Ilmiah - Mazid, Arini Rufaida; ARYANTI, OKTAVIA; ARIFIN, ZAENAL; Suwarno, Muji (Mathieu : Journal of Mathematics Education and Learning, 2026)
This study bibliometrically analyzes the relationship between critical thinking and mathematical anxiety using Google Scholar data through Publish or Perish, covering 2020–2026. From 983 documents, 46 articles were analyzed using VOSviewer to map publication trends, author collaboration networks, and keyword clustering. Publication trends were fluctuating, with a decline in 2021 attributed to the COVID-19 pandemic, followed by recovery in subsequent years. Publications were dominated by Indonesian local journals, with Miatun, A. as the most productive author. Two keyword clusters were identified, with "student", "critical thinking", and "mathematical anxiety" as conceptual cores. Research focus has shifted from general conceptual studies toward a more integrative cognitive-psychological approach. Density visualization indicates that mathematical anxiety remains at a low saturation level, offering broad opportunities for further exploration. This study is expected to serve as a roadmap for advancing research in mathematics education.